Funções hiperbólicas: história, conceito e aplicação - (:unkn) unknown (UNIVERSIDADE FEDERAL DO AMAZONAS, 2013)
This dissertation is a study of a class of functions, which behavior suggests an analogy with the trigonometric functions, that are the hyberbolic functions. These functions appear naturally from the simple combinations of exponential functions ex2 and e-x2, the hyperbolic cosine and the hyperbolic sine are the both most important, they are the result of the sum and the direct di_erence between them. The history will be addressed, some mathematicians and their contributions will be refered, the conceptualization, the development of its properties, its relations with the trigonometric functions, the derivative, the integral, its graphic and explore its aplication.
Keywords: Funções hiperbólicas; Funções trigonométricas; Funções exponenciais; CIÊNCIAS EXATAS E DA TERRA: MATEMÁTICA